Efficient access to sp3-rich tricyclic amine scaffolds through Diels–Alder reactions of azide-containing silyloxydienes. Issue 26 (30th June 2016) - McLeod, Michael C.; Aubé, Jeffrey
Abstract: The preparation of sp 3 -rich scaffolds to obtain more natural product–like libraries for incorporation into screening decks is challenging. Here, we describe the use of a Diels–Alder reaction between an enone and an azide-containing silyloxydiene to gain efficient access to complex tricyclic amine scaffolds. Derivatization of these scaffolds provided a library of 80 amines, amides, sulfonamides, quinolines and indolenines, all in >20 mg quantities and >90% purities. These library compounds displayed properties more similar to alkaloid natural products than to drugs and commercial drug-like libraries, as shown by a high proportion of sp 3 carbon centers. Graphical abstract: